Visual comfort under daylighting conditions in two school classrooms in Malaysia - Sojoudi, Sahar (2014)
Light has important visual and non-visual effects on humans and high-quality light should therefore be supplied inside buildings in sufficient quantities. It is thus important to take into account the visual and non-visual effects of light and energyefficiency when designing fenestrations for school classrooms. Conventional tropical school building design in Malaysia is experiencing a new paradigm by way of its environmental response to improve the lighting ambiance and a user’s comfort by exploiting daylighting. This research was focused on assessing existing visual comfort, illuminance levels, and users’ preference of daylighting applied in a tropical country like Malaysia based on their windows by comparing those factors between two schools with different windows. Two similar classrooms from two different schools in the same geographic location with different opening provisions were compared.Daylighting evaluation was done through field measurement; computer simulation and user survey. Visual comfort level in one classroom for both schools collected at 8am until 1pm. Light measurements were indicated using 10 data loggers (HOBO devices) were at 9 different locations in the classroom and one outdoor. Computer simulations generated under ‘10K CIE Overcast Sky’ file were used to predict daylighting erformance. Furthermore, the survey carried out measured user’s comfort and awareness. The response were recorded via questionnaires issued to them at each of the selected classrooms. The survey is performed during operation morning hours of the secondary schools. In conclusion, findings from the field measurement showed that below minimum recommended illumination for reading (300 Lux) was indicated at 45 percent of the classroom in Taman Desaminium secondary school. Thus more complaints were recorded by an occupational survey at the Taman Desaminium school in terms of high level of contrast and glumness from the users. As the Seri Serdang secondary school, field measurement showed that below minimum recommended illumination for reading is 33 percent and 55.55 percent of classroom is definitely in the recommended illumination for reading (300 -500 Lux).